2020
DOI: 10.1088/1361-6587/ab9a11
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of 2/1 fishbone-like modes by trapped energetic ions

Abstract: A new branch of the m/n = 2/1 fishbone-like mode is found to be excitated by trapped energetic ions when the tearing mode is unstable. An energy-principle-based dispersion relation is derived and analyzed, which incorporates the wave-particle resonance and the resistive layer physics. Once the beta amplitude of trapped energetic ions exceeds a critical value, 2/1 fishbone-like instabilities would appear. The mode transition from tearing mode to 2/1 fishbone-like mode will be triggered with the increasing beta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…When S M > 10 5 , the critical beta β cr TEI0 is almost unchanged as S M increases. This further confirms the above result and is consistent with previous theoretical work [9,10,30]. As pointed out above, the value of S M from experimental parameters is sufficiently large that the critical beta, β cr TEI0 , remains unchanged with increasing S M .…”
Section: Effects Of the Electron Temperaturesupporting
confidence: 93%
See 2 more Smart Citations
“…When S M > 10 5 , the critical beta β cr TEI0 is almost unchanged as S M increases. This further confirms the above result and is consistent with previous theoretical work [9,10,30]. As pointed out above, the value of S M from experimental parameters is sufficiently large that the critical beta, β cr TEI0 , remains unchanged with increasing S M .…”
Section: Effects Of the Electron Temperaturesupporting
confidence: 93%
“…√ m e 2/3 T e ( r) [34] is the slowingdown critical energy and β TEI ( r) = β TEI0 exp(− r/ σ i ) [30].…”
Section: Dispersion Relationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, frequency chirping up and back down of NTMs has also been observed on DIII-D, where the chirping time is a few milliseconds, and has been suggested that trapped energetic ions may be responsible for this [21]. Some efforts [22][23][24] have been made to theoretcially understand the underlying physics. In [22], it was pointed out that resonance between trapped energetic ions and rotating NTMs provides a torque to accelerate the rotation of the NTMs; however, the estimated chirping time is much longer than that observed in the experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In [22], it was pointed out that resonance between trapped energetic ions and rotating NTMs provides a torque to accelerate the rotation of the NTMs; however, the estimated chirping time is much longer than that observed in the experiments. Two recent articles [23,24] have described the bursting and chirping of tearing modes on HL-2A. In [23], it was shown that resonance between trapped energetic ions and tearing modes can drive a fishbone-like mode.…”
Section: Introductionmentioning
confidence: 99%